Enrichment planting under restored riparian forests: neither for all species nor for all situations - dos Santos, Wander Laizo [UNESP]; de Oliveira, Carlos Delano Cardoso; Durigan, Giselda [UNESP] (Elsevier, 2025)
In ecological restoration, adaptive management can assist arrested forest recovery and biodiversity losses. Enrichment planting has been suggested to increase biodiversity, but its effectiveness is still not validated. We assessed the performance (survival and growth) of 2000 seedlings (nursery-grown and acclimated to enrichment conditions) from five shade-tolerant native tree species in enrichment planting treatments. Seedlings were planted within riparian Atlantic Forests undergoing restoration (8 to 20 years old) — specifically between planting rows, in failures, beneath girdled trees, and in open areas (control). After six years, the seedlings' survival surpassed 65 % for most species in the understory, but annual growth rates were generally low (averaging 2 mm in stem diameter, 13 cm in height, and 7 cm in crown diameter). Deciduous species grew faster in the open but did not differ from evergreen species in the understory. Growth differences diverged more between species than between enrichment treatments. Using large and hardened seedlings of shade-tolerant species likely increased survival rates, demonstrating that enrichment plantings can be successful. However, selecting the right species to plant is crucial, requiring a good knowledge of a species' response and effect traits to predict their performance under enrichment conditions. Despite being possible, the biodiversity outcomes of enrichment planting remain in question due to the high costs and slow growth. Thus, we recommend enrichment plantings to increase plant diversity in restored forests only where the spontaneous arrival of new species is constrained by landscape features or when increasing populations of particular target species is desirable.